Prediction of the pile behaviour under dynamic loading using embedded strain sensor technology - Štrukelj, Andrej (Acta geotechnica Slovenica, 2009)
A standard dynamic loading test of the pile was performed on the highway section Slivnica - Hajdina near Maribor, Slovenia. Parallel to standard testing procedures the new monitoring technology based on specially developed strain sensors installed inside the pile body along the pile axis was introduced. On the basis of the measured results the normal strains along the pile axis were measured. Taking into consideration the elastic modulus of the concrete the normal stresses in the axial direction of the pile were also calculated and afterwards the shear stresses along the pile shaft have been estimated as well as the normal stresses below the pile toe. The estimation was made by considering a constant value for the pile diameter. The measured results were also compared with the computer simulation of the pile and the soil behaviour during all the successive test phases. The strain measurements inside the pile body during the standard dynamic loading test in present case did not have the purpose of developing an alternative method of pile loading tests. The presented monitoring technology proved itself as a very accurate and consistent. It gave in the first place the possibility of a closer look at the strains and stresses of the most unapproachable parts of different types of concrete structure elements especially piles and other types of deep foundations.
Keywords: deformacije; metoda končnih elementov; obremenitev; piloti; temeljenje